Evaluation of Photo Math in Teaching Elementary Algebra - Igcasama, Raymund Medrano; Ramirez, Dexter T.; Salanap, Naome P. (LPPM Undiksha, 2020)
This study aims to evaluate â€œPhoto Mathâ€ in teaching Elementary Algebra.Â Specifically, it aimed to identify the effect of teaching Elementary Algebra with the use of â€œPhoto Mathâ€. To achieved these objectives, the researchers used qualitative, quantitative and experimental design. This was conducted through a separate teaching demo in Elementary Algebra of the two Grade 7 sections. Pre-test was administered before the conduct of the demo and post-test after the teaching demo. The study showed that there was a significant difference between the pre-test and post-test results of the section with â€œPhoto Mathâ€ as intervention. Moreover, there was also a significant difference between the pre-test and post-test results of the section without the said application as intervention. However, it showed that there was no significant difference between the two section. The first section showed that there was an effect to the performance of the students when â€œPhoto Mathâ€ was applied as teaching tool but it was not fully claimed when compared with the traditional method of teaching. This was because the sample size of the study is small so it was recommended to have a larger number of sample size to see the effect of â€œPhoto Mathâ€ in teaching Elementary Algebra. The study implied that Photo math as a teaching tool had an effect on teaching elementary algebra.